Influence of Training Lessons on Change of Value-Rational Component of Psychological Culture of Students of Early Young age - Pavlovna Kondratyeva, Natalia; Vladimirovna Vardanyan, Yulia; Sergeevna Dementieva, Maria; Valeryevna Vardanyan, Lyudmila; ., . (International Journal of Engineering and Technology, 2018)
The purpose of the study is to determine the features of the value-semantic component of the psychological culture of students in early adolescence and the effect of training sessions on their change. The experimental study included the following steps: verifying, scheming and testing the training program. 32 students aged 16-17 were participants in the research. The main research methods were: theoretical, experimental, and diagnostic, as well as methods of mathematical data treatment. The paper highlights the features of the nature of the relations, values and meaningful orientations of students in early adolescence. Further, it gives the main aspects and results of approbation of the training and development of the value-rational component of the psychological culture of teenagers. It is proved that the implementation of a specially developed training program, including exercises for the development of a positive attitude towards others and oneself, meaningful orientations, and an awareness of the value orientations in life, contributes to the development of the value-rational component of the psychological culture of teenagers. The materials of this paper are of practical value for educational psychologists.Â Â